Answer:
![(x^2-3^2)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-3%5E2%29%28x%2B3%29)
![(x-3)(x+3)(x+3)](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%28x%2B3%29)
![(x-3)(x+3)^2](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%5E2)
Step-by-step explanation:
Given
![(x^2-9)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-9%29%28x%2B3%29)
Required
Select 3 equivalent expressions
![(x^2-9)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-9%29%28x%2B3%29)
Express 9 as 3^2
--- This is one equivalent expression
Take
as difference of two squares
-- This is another equivalent expression:
Solving further:
becomes
-- This is another equivalent expression:
Hence, the equivalent expressions are:
![(x^2-3^2)(x+3)](https://tex.z-dn.net/?f=%28x%5E2-3%5E2%29%28x%2B3%29)
![(x-3)(x+3)(x+3)](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%28x%2B3%29)
![(x-3)(x+3)^2](https://tex.z-dn.net/?f=%28x-3%29%28x%2B3%29%5E2)
The negative sign show the change in direction, that is the opposite side of the value.
In the number line, 1 is the opposite of -1, that is the digit from the left side is the opposite value of the right side.
Consider an object P is moving in positive x direction than on moving the object into its opposite direction, it will move along the negative x axis.
Answer : A) -
If it gives you your total, and another number, divide the 2
example:
25 • x = 75
75/25= 3
x=3
1:2 means for every 1 drop of green there was 2 blue
6/2 = 3
3 drops of green
-3^6 = -729
-729 +(-4+7)(2)
-729 +(3)(2)
-729 + 6
-723
<em>hope it helps :)</em>
(ps: the result of -3^6 is not +729, the expression that would give this result is (-3)^6